PERSONALITY THEORY IN INTEGRATIVE PERSONALITY-ORIENTED RECONSTRUCTIVE PSYCHOTHERAPY - V. I. Kurpatov; S. A. Osipova; V. V. Kolchina (Неврология, нейропсихиатрия, психосоматика, 2010)
The state-of-the-art of psychotherapy is associated with the integration of various assumptions and theories of personality, psychotherapeutic approaches. V.N. Myasishchev's theory of personality relations in association with its universality, as well as pathogenetic psychotherapy may be the basis for the integration of other methods of psychotherapy.